Treatment of patellofemoral pain syndrome with neuromuscular training: A brief review (Research, Society and Development, 2021)
Patellofemoral pain syndrome is a pathology that causes pain and discomfort in the posterior region of the patella, compromising the strength, stability and functionality of the knee joint, affecting the performance of simple daily tasks in young adults and compromising performance in independent athletes of sex. With extensive literature, but still several gaps on forms of treatment that would be more effective in improving pain, functionality, stability and increased strength. The objective was to identify in the literature the type of treatment most effective in improving pain and functionality in the individual diagnosed with patellofemoral syndrome. This study carried out a literature review on studies related to treatment based on exercise and neuromuscular strengthening. The search was carried out in an electronic database. The electronic search resulted in 150 journals, after analyzing them, 10 studies met the defined inclusion criteria, adding 17 more articles on the pathology and anatomy of the knee. This study concluded that treatment protocols that involved strengthening exercises associated with quadriceps strengthening exercises, demonstrated greater effectiveness when compared individually, also concluding that individuals who remained active after the interventions did not experience pain again.